Immunologic characteristics of winter rye varieties - T. K. Sheshegova; L. M. Shchekleina; E. I. Utkina (Аграрная наука Евро-Северо-Востока)
Studies were conducted in 2010-2017. Under conditions of Kirov region onnatural and artificial epiphytoties 29 varieties of winter rye grown in Russian Federation and 20 perspective populations bred in FARC of North-East were investigated for resistance to snow mold, sclerotinia, root rot, ear fusarium, ergot, septoriosis, rhynchosporium, and some types of rust. Modeling the pathocenoses the methods of S.S. Shain (1987),T.K.Sheshegova and L.I. Kedrova (2003) and others were used. Varieties Krona, Chulpan 7, Pamyati Kunakbaeva, Volkhova, Rada, Grafinya, Falenskaya 4, Leda, Nioba, Grafit, C-30/07, and Perepel have relative resistance against two or more diseases. These varieties could be used as gene sources in different breeding programs. It has been established that winter rye varieties bred in FARC of North-East have higher resistance level to snow mold that is proved by their rate of re-growth after defeat by artificial inoculation Microdochium nivale (Fr.) Sam.et.Hall. (61.4% on the average among varieties) but they are more susceptible to stem rust ( the affection degree under conditions of natural epiphytoties is 40.0% on the average). Varieties Rada, Flora, Rushnik, Grafinya, Nioba, and Leda were noted for productivity, they 0.08-0.26 t/ha exceeded standard Falenskaya 4 for three years on the average. Using the method of biotypic selection on ergot and ear fusariosis complex infectious background three populations were created: FK 7-10/12, Graphit, and Gratsiya. In some years these varieties exceeded standard variety Falenskaya 4 on productivity, they were distinguished by high winter hardiness, large grain size, and resistance to lodging.